Asynchronous pre- and postsynaptic activity induces associative long-term depression in area CA1 of the rat hippocampus in vitro. - Debanne, D (1994)
Associative long-term depression (LTD) was induced in hippocampal slice cultures with repeated low-frequency (0.3 Hz) stimulation of the Schaffer collateral pathway, only when such stimuli were preceded by intracellular injection of brief depolarizing current pulses in the postsynaptic CA1 pyramidal cell. The decrease in excitatory postsynaptic potential amplitude lasted > 30 min, could be reversed by induction of potentiation, could be induced at previously potentiated inputs, was input-specific, and did not require activation or potentiation of other inputs. The magnitude of the depression depended upon the time interval between depolarization and stimulation and upon the duration of the depolarization pulse. LTD was not observed in neurons impaled with electrodes containing a Ca2+ chelator. LTD could not be induced in the presence of an N-methyl-D-aspartate receptor antagonist, suggesting that voltage-dependent Ca2+ influx is necessary but not sufficient for LTD induction. We conclude that associative LTD results when synaptic activity follows postsynaptic depolarization within a circumscribed time window.